SLC19A3 Gene Defects Sorting the Phenotype and Acronyms: Review - Alfadhel, Majid; Tabarki, Brahim (Neuropediatrics, 2018)
Thiamine metabolism dysfunction syndrome type 2 is also known by other terms including: “SCL19A3 gene defect,” “biotin-responsive basal ganglia disease” (BBGD), and “biotin-thiamine–responsive basal ganglia disease” (BTBGD). The worldwide incidence and prevalence of this disorder are unknown, but the syndrome has primarily been reported in Saudi Arabia (52% of reported cases). It is caused by a defect in thiamine transporter 2 (hTHTR2), which is encoded by the SLC19A3 gene. The clinical presentations of these syndromes are heterogeneous and are likely related to the age of onset. They can be classified into three major categories: classical childhood BBGD; early-infantile Leigh-like syndrome/atypical infantile spasms; and adult Wernicke's-like encephalopathy. These variable phenotypes have common features in that all are triggered by stressors, such as fever, trauma, or vaccinations. Affected brain areas include the basal ganglia, cerebral cortex, thalamus, and periaqueductal regions. Free thiamine is a potential biomarker for diagnosis and monitoring of treatment. Definitive diagnosis is usually made by molecular testing for the SLC19A3 gene defect, and treatment consists of thiamine alone or in combination with biotin for life. In this report, we review all reported cases of the SLC19A3 gene defect, discuss the history, epidemiology, metabolic pathways, clinical phenotypes, biochemical abnormalities, brain pathology, diagnosis, genetic issues, and treatment of this devastating disorder. Finally, we recommend instituting an international registry to further the basic scientific and clinical research to elucidate multiple unanswered questions about SLC19A3 gene syndromes.
Keywords: SCL19A3 gene defect; biotin-responsive basal ganglia disease; BBGD; biotin-thiamine–responsive basal ganglia disease; BTBGD; thiamine metabolism dysfunction syndrome 2